Clinical and Genetic Studies of Limb Girdle Muscular Dystrophy: Reports of Two Cases (Journal of Enam Medical College, 2022)
Limb girdle muscular dystrophy (LGMD) presents with weakness and wasting of muscles, initially appear at proximal group of pelvic and shoulder girdles and inherited by an autosomal recessive disorder mainly and rarely autosomal dominant trait. We report two young girls of limb girdle muscular dystrophy (LGMD), who presented with gradual onset of weakness in proximal muscle of all four limbs. There was positive family history in one girl. Neurological examination revealed pseudo hypertrophy of both calves, hypotonia in all four limbs, muscle power diminished, more on proximally. All deep tendon reflexes were diminished with planters bilateral flexors. Gower sign was positive and winging of scapula was also present. Electromyography (EMG) showed myopathic pattern. Both had elevated creatinine phosphokinase levels and finally genetic study confirmed the diagnosis.J Enam Med Col 2020; 10(3): 190-194